2001
DOI: 10.1016/s0014-5793(01)02772-7
|View full text |Cite
|
Sign up to set email alerts
|

Differences in proton leak kinetics, but not in UCP3 protein content, in subsarcolemmal and intermyofibrillar skeletal muscle mitochondria from fed and fasted rats

Abstract: We have investigated the effect of 24-h fasting on basal proton leak and uncoupling protein (UCP) 3 expression at the protein level in subsarcolemmal and intermyofibrillar skeletal muscle mitochondria. In fed rats, the two mitochondrial populations displayed different proton leak, but the same protein content of UCP3. In addition, 24-h fasting, both at 24 and 29 degrees C, induced an increase in proton leak only in subsarcolemmal mitochondria, while UCP3 content increased in both the populations. From the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
19
2

Year Published

2002
2002
2012
2012

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 35 publications
(45 reference statements)
9
19
2
Order By: Relevance
“…Our data show that the differential expression of UCP3 contributes further to the unique constitution of each mitochondrial subfraction. In contrast to our findings, Jimenez et al (32) have detailed a higher basal UCP3 expression in the SS subfraction isolated from mouse TA, whereas Iossa et al (28) found no difference in rat skeletal muscle UCP3 content between IMF and SS mitochondria. We cannot explain these discrepant results other than to propose either species (32) or methodological differences (28).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our data show that the differential expression of UCP3 contributes further to the unique constitution of each mitochondrial subfraction. In contrast to our findings, Jimenez et al (32) have detailed a higher basal UCP3 expression in the SS subfraction isolated from mouse TA, whereas Iossa et al (28) found no difference in rat skeletal muscle UCP3 content between IMF and SS mitochondria. We cannot explain these discrepant results other than to propose either species (32) or methodological differences (28).…”
Section: Discussioncontrasting
confidence: 99%
“…State 4 mitochondrial respiration rates were 2.6-fold greater in IMF mitochondria than those observed in the SS mitochondrial subfraction (P Ͻ 0.05; Fig. 1A), in agreement with previous studies (10,28,37). In contrast, UCP3 protein levels were only 1.3-fold greater in IMF mitochondria, compared with the SS subfraction (P Ͻ 0.05; Fig.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Hind leg muscles were rapidly removed and used for the preparation of subsarcolemmal (SS) and intermyofibrillar (IMF) mitochondria, as described previously (14). Immediately after the isolation, aliquots of mitochondria were frozen and stored at Ϫ80°C for the determination of uncoupling protein 3 (UCP3) by Western blotting using UCP3 antibody (Chemicon International, Temecula, CA), as previously described (15,16). Measurements of mitochondrial respiration and basal and palmitateinduced proton leak.…”
Section: Methodsmentioning
confidence: 99%
“…This hypothesis of a UCP-mediated state of partial uncoupling in fasted muscle is, however, at odds to that expected for any putative mediator of thermogenesis in a well-established condition of energy conservation at the whole body level [41] and in the skeletal muscle [57]. In particular, fastinginduced increases in UCP2 and UCP3 expressions in skeletal muscle occur without changes in kinetics of proton conductance pathway in isolated mitochondria [58,59] and without changes in the overall state of mitochondrial energy coupling in the hindlimb of awake animals, as assessed by noninvasive 13C/31P NMR spectroscopic approaches [60]. (iii) High-fat feeding paradox: Similarly in humans, increasing fat in the diet leads to increased skeletal muscle UCP3 expression but not in mitochondrial uncoupling, as assessed by the lack of any changes in the rate of muscle phosphocreatine resynthesis during conditions of maximal flux through oxidative phosphorylation [61].…”
Section: Ucp1-homologues: Are They Mediators Of Thermogenesis?mentioning
confidence: 96%